ธรณีสัณฐานภูมิประเทศแบดแลนด์บริเวณละลุ ตำบลทัพราช อำเภอตาพระยา จังหวัดสระแก้ว - ยวงเงิน ณัฐพร; กาญจนสุธรรม สุพรรณ; เอี่ยมหน่อ อภิสิทธิ์; นวลฉวี แก้ว (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2015)
งานวิจัยนี้มีวัตถุประสงค์ในการศึกษาลักษณะสัณฐาน กระบวนการเกิดและ โครงสร้างตะกอนของอนุสัณฐานภูมิประเทศแบดแลนด์ บริเวณละลุในลุ่มน้ำห้วยยาง ตอนบน บ้านหนองผักแว่น ตำบลทัพราช อำเภอตาพระยา จังหวัดสระแก้ว โดยศึกษาจาก แผนที่ภูมิประเทศมาตราส่วน 1 : 50,000 แผนที่ธรณีวิทยา รูปถ่ายทางอากาศ ภาพถ่าย ดาวเทียม Landsat ภาพจากยานไร้คนขับ (UAV) ผลการวิเคราะห์ในห้องปฏิบัติการ ข้อมูล จากกรมทรัพยากรธรณีและจากการศึกษาในภาคสนาม ผลจากการศึกษาพบว่า อนุสัณฐานภูมิประเทศแบดแลนด์บริเวณละลุ ได้แก่ หลุมยุบ หน้าผา กำแพงดิน เสาดินและตอดิน พบในบริเวณที่ราบระหว่างภูเขาแคบ ๆ ซึ่งมีภูมิประเทศเป็นลาดเชิงเขา ที่เกิดจากตะกอนเศษหินเชิงเขา และการผุพังอยู่กับที่ของหินฐาน โดยมีน้ำฝนและทางน้ำ สาขาของลุ่มน้ำห้วยยางตอนบนกัดเซาะทั้งในแนวราบและแนวลึก ในบริเวณที่พบ มักพบ รอยแตก รอยร้าวของชั้นตะกอน สัณฐานของแต่ละอนุสัณฐานประกอบด้วยรูปร่าง ความ กว้าง ความยาว ความสูง ความลึก ลักษณะผิวหน้าของสัณฐาน ซึ่งมีความแตกต่างกันตาม ลักษณะโครงสร้างของตะกอนในแต่ละชั้น อันเป็นผลมาจากวัตถุต้นกำเนิดตะกอน ซึ่งเป็น หน่วยหินพระวิหารและหน่วยหินภูกระดึงที่ให้สีตะกอนเป็นสีเหลือง น้ำตาลและสีแดง โดยมีเนื้อตะกอนส่วนใหญ่เป็นเนื้อค่อนข้างละเอียดถึงตะกอนเนื้อร่วน เมื่อผ่านการชะล้าง ทำให้เกิดการสะสมแร่ดินเหนียว ทำให้ตะกอนชั้นล่าง ๆ มีเนื้อตะกอนละเอียดกว่าชั้นบน ๆ จึงส่งผลให้ความสามารถในการแทรกซึมของน้ำมีน้อย น้ำจึงไหลในแนวราบใต้พื้นดิน ทำให้ เกิดโพรงใต้ชั้นตะกอนและยุบพังลงมากลายเป็นจุดเริ่มต้นองหลุมยุบ หลังจากนั้น หลุมยุบ จะพัฒนาเป็นหน้าผา กำแพงดิน เสาดินและตอดิน และทำให้เกิดภูมิประเทศแบดแลนด์ บริเวณผิวหน้าส่วนใหญ่ของแต่ละอนุสัณฐานไม่เรียบ มีร่อง หลืบ เสาและรูโพรง และมัก พบทางน้ำไหลผ่านบริเวณส่วนล่างของสัณฐาน ยกเว้นอนุสัณฐานตอดินจะมีผิวหน้าของ สัณฐานเรียบ เพราะผ่านการพัฒนาตัวยาวนานกว่าอนุสัณฐานอื่น ๆ THE BADLANDS MORPHOLOGY IN LALU AREA : THE UPPER HUAY YANG BASIN, TUBRAJ, AMPHOE TA PHRAYA SA KAEO PROVINCE This research aims to study morphology, formation and sediments structure of badlands morphology in Lalu area : the upper Huay Yang basin, Tubraj , Ta phraya Sakeao Province. Different tools and instruments are used to collect different types of data i.e.topographic maps, with scele of the scale is 1 : 50,000, geography maps, Arial Photography, Landsats satellite photography, unmanned Aerials, lab reports and data from both field trip and Department of Mineral resources. This research showed that sub landforms of badlands morphology in Lalu area are sinkholes, cliffs, soil walls, soil columns and stack soil. Sub landforms are found at the intermontane narrow plain, foothill slopes, which is formed by colluvial deposits and residual deposits Moreover, these sub landforms are eroded both horizontally and vertically by raindrops and water from Huay Yang basin. Surrounding area of sub landforms features many cracks on rocky the sediment layer. The study of components of each sub landform comprises of shape, width, length, height, depth and land surface. Land surfaces were varied depending on broken seilene on the structure of sediment in each layer which came from their parent materials. Parent materials of sub landforms of Badlands morphology in LALU area are Phra Wihan formation and Phu Kradung formation which created their sediments in yellow, brown and red colors and they have very fine and fine granted texture. Leaching process forms the accumulation of clay and mud, so the sediment more granted texture than the upper lower one ; therefore, has a few of water percolation. Only alittle water can run through on the surface, so it run horizontal beneath the run-on shiteree ground, This process created holes at the sediment layer. Finally, a hole collapse and this is the original state of the sinkhole process. After that, the sinkhole transforms in to cliffs, soil walls, soil columns, stack soil and badlands Surface of each sub landform feature rough not smooth rill columns holes and water channel frequently found at the bottom Whilst surface of stack soil is smooth because its development main clause occurred before the others.